The effect of polymer concentration on the development of polysulfone (PSU) membrane for carbon dioxide(CO2)and methane (CH4) separation - Siti Aisah, Jamil (2010)
Membrane based gas separation process technology has been recognized as one of the most efficient and advanced unit operation for the gas separation process.The main problem in membrane gas separation is the tradeoff between the permeability and selectivity. The effect of Polysulfone (PSU) polymer concentration was studied to find out the optimum polymer concentration and gives the best performance to the developed membrane. Asymmetric gas separation membranes were prepared from polysulfone (PSU)polymer with three different polymer concentration. Casting solution in this study consisted of polysulfone (PSU)as a polymer,1-methyl-2-pyrrolidone (NMP)as a solvent while distilled water was used as non solvent additive.The prepared membrane was tested using permeation test unit by using CO2 and CH4 as a test gaseous.From the experimental result,the highest selectivity had been achieved at polymer concentration of 32.5% with the selectivity was 2.56 while for the lowest selectivity had been found at polymer concentration of 22% where the selectivity was 1.42.The optimum selectivity was found at pressure 2 bars.The membranes were further characterized by scanning electron microscopy(SEM)to investigate the morphology of membranes respectively. As a conclusion,the polymer concentration parameter is given big effect to the performance of membrane.